2022
DOI: 10.32604/cmc.2022.017522
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Unusual Activities Recognition Using Deep Learning in Academia

Abstract: In the current era, automatic surveillance has become an active research problem due to its vast real-world applications, particularly for maintaining law and order. A continuous manual monitoring of human activities is a tedious task. The use of cameras and automatic detection of unusual surveillance activity has been growing exponentially over the last few years. Various computer vision techniques have been applied for observation and surveillance of real-world activities. This research study focuses on dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…They created a dataset for out-of-the-ordinary behaviors during the examination and suggested a deeplearning model to detect them. This work's data-augmentation process included rotation range, width shift, flipping the data horizontally or vertically, and rescaling [20].…”
Section: Related Workmentioning
confidence: 99%
“…They created a dataset for out-of-the-ordinary behaviors during the examination and suggested a deeplearning model to detect them. This work's data-augmentation process included rotation range, width shift, flipping the data horizontally or vertically, and rescaling [20].…”
Section: Related Workmentioning
confidence: 99%
“…First started with cheating activities in physical exams, then moved on to online exam cheating, and finally in those studies where both online and physical exams were taken using machine learning, deep learning, and hybrid models. Ramzan et al [8] identified and recognized anomalous activities of students in exam rooms, to assist invigilators in observing students from cheating or employing unfair techniques. Their research compared the effectiveness of several CNN networks that have been used to look for unusual physical exam activity.…”
Section: Introductionmentioning
confidence: 99%
“…Situations such as an abandoned object, a patient falling in the hospital, students cheating during exams [ 1 ], driver drowsiness [ 2 ], road accidents, traffic rules violations, and in public places such as slapping, punching, hitting, firing, abuse, snatching, fighting, terrorism, robbery, illegal parking, fire disaster. According to World Health Organization (WHO) statistics, road accidents are currently one of the top ten reasons for death worldwide [ 3 ].…”
Section: Introductionmentioning
confidence: 99%